SIKAP PEREMPUAN MISKIN TERHADAP HUKUM YANG BERPIHAK PADA PEREMPUAN (Studi Di Kabupaten Cilacap) - Zulfatun Ni’mah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This qualitative research is studying the responds of poor women who have a child born out of wedlock to replacement of law about law relationship between a child born out of wedlock with his or father biological father. At first, Marriage Act rules that a child born out of wedlock is only have legal relation with his or her mother, but this rule has replaced by a new rule, it is Constitution Court Judgement No 41/PUU/2012 that says that a child born out of wedlock also have legal relation with his biological father. The result of research show that poor women who have a child born out of wedlock are don’t respond the new rule happily because of they think that law is a difficult and complicated affair. Need to some money to solve the problem by law. Beside it, they are avoid to meet and take a part to get affair with the biological father of their child, a person who ever leave them in suffer because make them pragnanc but unresponsible.